Hidrolisados proteicos em rações extrusadas para tilápia: produtividade e qualidade dos péletes - Oliveira, Renan Gustavo de (2024)
The growth of aquaculture has boosted feed production and studies focused on aquatic nutrition, mainly on the inclusion of new products in diets, aiming to improve production performance. This work aimed to evaluate whether the inclusion of enzymatic hydrolyzed feathers (HEP) and hydrolyzed chicken protein (PHF) in extruded feed for tilapia improves the extruder's productivity rates and the quality of the pellets. For this, three diets were formulated (control, HEP and PHF), mixed, processed in an Exteec® Ex-30R 40 kg/h extruder, dried in an oven and subjected to evaluations. Six extrusions (replicates) were performed for each diet, with six repetitions every three minutes. We analyze the indices that evaluate the extruder's feed productivity and the physical and chemical stability of the pellets. Analysis of variance was performed in order to identify differences in means between treatments for all analyses. Dry feed production and water consumption decreased significantly in diets with inclusion, at the same time that energy consumption and the consumption/production ratio increased. Regarding physical stability indices, there was a decrease in density and a significant increase in expansion with inclusions. The amount of fines was lower for the HEP diet and similar between control and PHF. Feed buoyancy was 100% over 20 minutes. There was no difference in the hardness of the pellets. For the chemical stability of the pellets, similar results for extrusion humidity and water activity, with a decrease in diets containing hydrolysates. Total phosphorus loss by leaching was greater for HEP and equal for control and HEP, with statistical differences. For total ammonia, the control diet had the highest loss and those containing hydrolysates were similar. The control diet presented smaller and larger air chambers, and the diets containing hydrolysates presented smaller chambers with different shapes in the microstructure of the pellets. It is concluded that diets including protein hydrolysates in extruded feeds for tilapia harm the extruder's productivity indices, due to greater energy expenditure and lower productivity, significantly altering the physical stability indices of the pellets, reducing density and increasing expansion, and improves chemical stability indices, with reduced humidity, water activity and ammonia loss through leaching.